A preliminary study of using polycyclic aromatic hydrocarbons as chemical tracers for traceability in soybean products. (January 2015) - Pongpiachan, Siwatt
Abstract: Polycyclic Aromatic Hydrocarbons (PAHs) are a class of very stable organic molecules made up of only carbon and hydrogen and contain two to eight fused aromatic rings. PAHs are formed during incomplete combustion of organic materials such as fossil fuels, coke and wood. PAHs can be found in environment, the atmosphere, surface water, sediment, soil, food and in lipid tissues of both aquatic and terrestrial organisms. Natural emission sources of PAHs into the atmosphere include emissions from forest fires and volcanoes. Anthropogenic emission sources include combustion and industrial production. Incomplete combustion from motor vehicles, domestic heating and forest fires are major sources of PAHs in the atmosphere. Assuming that each region has different types of PAH emission sources, it seems rationale to hypothesize that the fingerprint of PAHs in agricultural products has its own unique locality characteristic. Since the food traceability is extremely crucial for food business, one can use PAH profile extracts from agricultural products to identify the originality. Three groups of soybean were classified according to the planting areas. In conclusion, soybean from three different countries (i.e. Thailand, Taiwan, Indonesia) can successfully be identified with the assistance of ANOVA and three-dimensional plots of binary diagnostic ratios of PAHs. Highlights: PAHs can be applied as alternative proxy for traceability of soybean products. Thailand soybean products have unique fingerprints of PAHs. The HI values falls in the "acceptable level" range.